Sonicating polycarboxylate-based superplasticizer for application in cementitious matrix - Silvestro,Laura (2023)
Abstract Sonication is widely used for nanomaterials dispersion in cementitious matrices. Polycarboxylate-based superplasticizer (SP) admixtures are usually incorporated in the aqueous nanomaterials suspension before sonication to improve the dispersion of these materials. Nevertheless, the effect of sonicating SP on its molecular structure or dispersing performance has not been fully investigated. This work assessed the effect of sonicating a commercial SP at 20 kHz, 750 W power, 50 or 80% amplitude, during 15 and 30 min. Initially, the sonication effect was evaluated in aqueous suspension by determining the SP size distribution (through dynamic light scattering – DLS) and zeta potential. Subsequently, the aqueous SP suspensions were used for Portland cement paste production. Rheological tests up to 120 minutes and compressive strength at 14 and 28 days were conducted. DLS and zeta potential results suggested that sonication reduce the size of SP chains. As a result, SP sonication increased the initial dynamic yield stress, viscosity, and hysteresis area of cement pastes. In contrast, SP sonication improved its time-dependent dispersing performance, resulting in pastes with reduced viscosity from 80 minutes onwards. Finally, SP sonication did not affect the compressive strength of cement pastes at 14 and 28 days of hydration. Overall, when SP is sonicated together with nanoparticles for application in cementitious matrices, the effect of sonicating the chemical admixture must be considered when the fresh-state properties of the composite are evaluated.